Atypical Electrophysiological Findings in a Patient with Acute Motor and Sensory Axonal Neuropathy - Versace, Viviana; Campostrini, Stefania; Tezzon, Frediano; Martignago, Sara; Kofler, Markus; Saltuari, Leopold; Sebastianelli, Luca; Nardone, Raffaele (Frontiers in Neurology, 2017)
Guillain-Barré syndrome (GBS) is an immune-mediated polyradiculoneuropathy with acute onset and rapid clinical worsening; early diagnosis and immunomodulating therapy can ameliorate the course of disease. During the first days, however, nerve conduction studies are not always conclusive. Here we describe a 73-year-old man presenting with progressive muscular weakness of the lower limbs, ascending to the upper limbs, accompanied by distal sensory disturbances. Neuroimaging of brain and spine and nerve conduction studies (NCS) were unremarkable; cerebrospinal fluid analysis revealed no albuminocytologic dissociation. Based on typical clinical features, and on positivity for serum GD1b-IgM antibodies, GBS with proximal conduction failure at multiple radicular levels was postulated, and a standard regime of intravenous immunoglobulin was administered. Four weeks later, the patient presented with flaccid tetraparesis, areflexia, and reduction of position sense, tingling paraesthesias and initial respiratory distress. Repeat NCS still revealed almost normal findings, except for the disappearance of right ulnar nerve F waves. A few days thereafter, the patient developed severe respiratory insufficiency requiring mechanical ventilation for two weeks. On day 50, NCS revealed for the first time markedly reduced compound muscle action potentials and sensory nerve action potentials in all tested nerves, without signs of demyelination; needle electromyography documented widespread denervation. The diagnosis of acute motor and sensory axonal neuropathy was made. After three months of intensive rehabilitation, the patient regained the ability to walk with little assistance and was discharged home. In conclusion, normal NCS findings up to several weeks do not exclude the diagnosis of GBS. Very proximal axonal conduction failure with late distal axonal degeneration should be taken into consideration, and electrodiagnostic follow-up examinations, even employing unusual techniques, are recommended over several weeks after disease onset.